2008
DOI: 10.1097/bsd.0b013e318093e5dc
|View full text |Cite
|
Sign up to set email alerts
|

Success of Lumbar Microdiscectomy in Patients With Modic Changes and Low-back Pain

Abstract: Therapeutic II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Similar to our study, Sorlie found that patients with Modic Type 1 changes had worse outcomes on the ODI and the EQ-5D after surgery[17]. In addition, a prospective case controlled study by Chin found that persons with IDH and no Modic changes did better after surgery [15]. These consistent findings suggest that Modic Type 1 changes may denote a pathologic source of radicular pain that is distinct from the disc herniation per se and therefore may not improve following discectomy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to our study, Sorlie found that patients with Modic Type 1 changes had worse outcomes on the ODI and the EQ-5D after surgery[17]. In addition, a prospective case controlled study by Chin found that persons with IDH and no Modic changes did better after surgery [15]. These consistent findings suggest that Modic Type 1 changes may denote a pathologic source of radicular pain that is distinct from the disc herniation per se and therefore may not improve following discectomy.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have looked at the effect of vertebral endplate or so-called Modic changes in patients with IDH and found that patients with baseline type 1 Modic changes have worse surgical outcomes [1517]. To date however, no studies have looked systematically at a broad range of MRI findings as potential predictors of outcome for both surgical and non-operatively treated patients with IDH.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatments for patients with LDH combined with MC at the same level have been discussed, but the outcomes remain controversial. Chin et al [ 15 ] reported significant improvement after nonfusion in minimally invasive discectomy, and suggested later fusion for younger patients, while Ohtori et al [ 16 ] suggested fusion surgery for patients with MC and hypermobility. Until now, few studies have reported surgical treatment for revision of LDH recurrence after PELD in patients with MC.…”
Section: Discussionmentioning
confidence: 99%
“…These studies attempting to predict outcomes of both conventional and microsurgical disc surgery based on disc size measured on MRI studies have produced inconsistent findings [ 16 ]. Location of the disc, disc space narrowing, the presence of larger eccentric disc fragments, the degree of narrowing or compromise of the axial spinal canal and associated bone changes, especially around the facet joints, are some of the findings examined to analyze how they affect outcomes [ 17 - 19 ] (Figure 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…A long-term eight-year MRI follow-up study showed that despite resolution of symptoms, frequently the post-procedure MRI did not change in as many as 65% of cases over 12 months and actually decreased in only 17.5% [ 16 ]. Preoperatively, finding more than 1/3 decrease in axial canal size was a better predictor of outcomes compared to only small herniations and Modic change with endoscopic or microdiscectomy lumbar surgery [ 16 - 17 ]. Large disc herniations and extruded or free fragments were clearly seen in cases with large decreases in canal dimensions [ 18 - 19 ].…”
Section: Reviewmentioning
confidence: 99%